Proposal to reduce waste in the cake production process using standard work and 5S - Molina Pasache, Mitzy Daniela (2025)
Small and medium-sized businesses represent 21% of Peru's Gross Domestic Product, which in turn accounts for 99.5% of formal employment in Peru. The bakery industry is part of this economic pillar; however, it faces various challenges in terms of productivity optimization. A bakery located in the La Libertad region was selected because its losses represent US$3,212 annually. The focus will be specifically on the "Pastel Queque Cono Tipo M" line, where a solution was developed based on the implementation of engineering tools: Work Standardization and 5S, with the objective of eradicating the root causes of losses. The result was a reduction in waste from 10% to 5% and a 16% reduction in cycle time. Economically, this project proves to be highly viable, with an IRR of 24% over a 2.4-year payback period.